Effect of Sintering on Structural and Magnetic Properties of Manganese Ferrite Nanoparticles - Yashpreet (My University, 2017)
Sintering is an essential step used in most of the synthesis processes. Magnetic nanoparticles are synthesized by variant of methods and in most of the cases they are subject to sintering to improve specific characteristics like hardness or magnetization. Co-precipitation is a very popular and easy technique to synthesize various nanoparticles, especially ferrites. Manganese ferrite nanoparticles are routinely synthesized by chemical coprecipitation technique. Effect of sintering on the structural and magnetic properties of manganese ferrite nanoparticles synthesized by coprecipitation method is not well understood. In this dissertation, effect of sintering on structural and magnetic properties of manganese ferrite nanoparticles has been studied. When sintered at 400 °C, as-synthesized MnFe2O4 nanoparticles decompose into - Fe2O3 and Mn3O4. Upon further heating at 600 °C, -Fe2O3 gets transformed into -Fe2O3. When MnFe2O4 is sintered at 900 °C, it decomposes into three crystallographic phases, i.e. - Fe2O3, Mn3O4 and Fe3O4. The corresponding changes in the magnetic properties are in good agreement with the observed changes in the structural properties of the MnFe2O4 due to sintering.
Master of Science -Physics
Keywords: Ferrites; Coprecipitation; Sintering